Assessment of motivation for using aesthetic medicine procedures and post-treatment satisfaction - Małolepsza, Aleksandra; Kister, Klaudia; Laskowski, Jakub; Szabrańska, Anna; Bronst, Paulina; Czechowska, Julia; Rosa, Lidka; Zach-Źródlak, Monika; Rektor, Natalia; Mazur, Magdalena (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Aesthetic medicine is a branch of medicine that focuses on improving the appearance through non-invasive or minimally invasive procedures. Over the years, many methods used to improving beauty and prevent aging were developed. People want not only to improve their physical appearance, but also their well-being and self-esteem. The aim of the study was to assess the motivation to use aesthetic medicine and satisfaction with the performed procedures. State of knowledge: Getting rid of wrinkles, sagging skin or unwanted fat deposits people feel more comfortable and satisfied with their bodies. Additionally, societal and cultural influences play a role in the popularity of aesthetic medicine. These interventions can also help with congenital deformities or experienced trauma. Motivation for using aesthetic medicine procedures can vary from person to person. It includes desire for youthful appearance, societal influences and beauty standards or career advancement. What is more, patient satisfaction is an important factor for successful therapy. Summary: In conclusion, the motivations for using aesthetic medicine procedures are multifaceted and vary from person to person. People seek these procedures for reasons such as enhancing self-confidence, desiring a more youthful appearance or improving emotional well-being. Aesthetic medicine can provide the opportunity to enhance self-image, boost confidence and improve overall quality of life.